2005
DOI: 10.1111/j.1460-9568.2005.04375.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced extracellular space in the brain of tenascin‐R‐ and HNK‐1‐sulphotransferase deficient mice

Abstract: Tenascin-R (TN-R), a large extracellular glycoprotein, is an important component of the adult brain's extracellular matrix (ECM); tenascin-C (TN-C) is expressed mainly during early development, while human natural killer 1 (HNK-1) is a sulphated carbohydrate epitope that attaches to these molecules, modifying their adhesive properties. To assess their influence on extracellular space (ECS) volume and geometry, we used the real-time iontophoretic method to measure ECS volume fraction alpha and tortuosity lambda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 49 publications
4
55
1
1
Order By: Relevance
“…It may be possible that degradation of hyaluronan led to a collapse of the space between some cells. Sykova and colleagues reported that knockout mice lacking tenascin-C, a key structural element of the brain ECM, exhibit a decrease in both the porosity and tortuosity [47]. It is possible that hyaluronan degradation reduced physical barriers to transport, but a simultaneous decrease in the porosity may have resulted in "lakes" at the interstices of some cells.…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible that degradation of hyaluronan led to a collapse of the space between some cells. Sykova and colleagues reported that knockout mice lacking tenascin-C, a key structural element of the brain ECM, exhibit a decrease in both the porosity and tortuosity [47]. It is possible that hyaluronan degradation reduced physical barriers to transport, but a simultaneous decrease in the porosity may have resulted in "lakes" at the interstices of some cells.…”
Section: Discussionmentioning
confidence: 99%
“…Values of ␣ (0.18 -0.19) and (1.61) found in wildtype mice in the present study can be compared with other in vivo studies on wild-type mouse cortex. For ages 3-6 months, Anděrová et al (2001) found ␣ ϭ 0.23, ϭ 1.67; for ages 6 -8 months, Syková et al (2005a) reported ␣ ϭ 0.20, ϭ 1.47-1.50; for ages 5-9 months, Syková et al (2005b) reported ␣ ϭ 0.17, ϭ 1.57. Variations among mouse strains probably account for the small differences in values.…”
Section: Comparison With Other Wild-type Mouse Studiesmentioning
confidence: 97%
“…For MRI measurements the animals were anesthetized with isoflurane (1.5% in a mixture consisting of 40% O 2 and 60% N 2 O) and placed in a heated mouse holder. Diffusion-weighted (DW) MRI measurements were performed as described previously (Syková et al, 2005), using an experimental MR spectrometer BIOSPEC 4.7 T system (Bruker) equipped with a 200 mT/m gradient system (190 s rise time) and a homemade head surface coil. Coronal slices, were acquired using the following parameters: ⌬ ϭ 30 ms, b-factors ϭ 136, 329, 675, 1035, 1481 and 1825 s/mm 2 , echo time ϭ 46 ms, repetition time ϭ 1200 ms, field of view 1.92 ϫ 1.92 cm 2 , matrix size ϭ 256 ϫ 128, four 0.8-mm-thick coronal slices, interslice distance ϭ 1.2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…ECM mol-ecules play a role in tissue cytoarchitecture by maintaining the optimal size of intercellular pores and by creating diffusion barriers (Roitbak and Syková, 1999;Zámecník et al, 2004;Syková et al, 2005). Diffusion barriers formed by myelin sheaths, glial processes and the ECM may channel the diffusion of molecules in a certain direction, so that diffusion is anisotropic, i.e., unequal along different axes (Prokopová et al, 1997;Vorísek and Syková, 1997).…”
Section: Introductionmentioning
confidence: 99%